Design and Build a Safe Security System Using RFID With e-KTP as a Tag and Monitoring With IoT-Based Esp32-Cam With Telegram Notifications: Rancang Bangun Sistem Pengaman Brankas Menggunakan RFID Dengan e-KTP Sebagai Tag dan Monitoring Dengan Esp32-Cam Berbasis IoT Dengan Notifikasi Telegram - Ashar, Abdul Adim; Saputra, Dwi Hadidjaja Rasjid (Universitas Muhammadiyah Sidoarjo, 2021)
Security is one form of convenience to protect archives or important objects such as land certificates, BPKB, and many others, and as a place to store these items a safe is created, with the development of technology, the safe is combined with several electronic components, a modern safe is created without a conventional key, only uses radio frequency identification which is already supported with an E-KTP and password to open it, uses a PIR sensor and an esp32 camera to find out who will access the safe and can be monitored every time. time via a smartphone using the telegram application, and also the telegram application can control the alarm if something suspicious is seen from the esp32 camera.